2020
DOI: 10.1017/s0007114520002986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper sulphate and coated copper sulphate addition on lactation performance, nutrient digestibility, ruminal fermentation and blood metabolites in dairy cows

Abstract: Coated copper sulfate (CCS) could be used as copper supplement in cows. To investigate the influences of copper sulfate (CS) and CCS on milk performance, nutrient digestion and rumen fermentation, fifty Holstein dairy cows were arranged in a randomized block design to five groups: control, CS addition (7.5 mg Cu/kg dry matter [DM] from CS) or CCS addition (5, 7.5 and 10 mg Cu/kg DM from CCS, respectively). When comparing copper source at equal inclusion rates (7.5 mg/kg DM), cows receiving CCS addition had hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…For example, the minimum dose of Cu to promote growth is over 250 mg/kg for piglets . Supplementing 125 mg/kg of Cu in poultry diets can increase growth; Cu oxidate nanoparticles (CuO–NPs) are also able to kill Salmonella in the gastrointestinal tract of poultry. , Besides, Cu is an essential element for rumen microorganisms in ruminants; dietary Cu sulfate improves milk performance and nutrients digestion and enhances ruminal fermentation at 10 mg/kg . Copper is also necessary for maintaining the minerals level and blood physiology and biochemistry in sheep, thus improving immunity functions and antioxidant ability. , Copper processing methods also impact its absorption efficiency.…”
Section: Copper and Livestockmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, the minimum dose of Cu to promote growth is over 250 mg/kg for piglets . Supplementing 125 mg/kg of Cu in poultry diets can increase growth; Cu oxidate nanoparticles (CuO–NPs) are also able to kill Salmonella in the gastrointestinal tract of poultry. , Besides, Cu is an essential element for rumen microorganisms in ruminants; dietary Cu sulfate improves milk performance and nutrients digestion and enhances ruminal fermentation at 10 mg/kg . Copper is also necessary for maintaining the minerals level and blood physiology and biochemistry in sheep, thus improving immunity functions and antioxidant ability. , Copper processing methods also impact its absorption efficiency.…”
Section: Copper and Livestockmentioning
confidence: 99%
“…Ruminants appear less able to cope with rising liver Cu concentration than monogastric counterparts, and sheep in general less able to cope with elevated Cu intake than cattle . For example, high Cu inhibits the growth of probiotics and causes diseases such as hemolysis in the rumen, , hepatic Cu concentration ranges from 3 to 1963 mg/kg with a mean of 473 mg/kg in the liver of cattle, dietary high Cu causes lysosome rupture and induces intravascular hemolysis, which further leads to hemoglobinuria, jaundice, and methemoglobinemia when the Cu concentration reaches saturation. , However, Strickland et al concluded that there are no histologically visible lesions in the architecture of bovine hepatocytes that could be attributed to Cu despite the supernutritional hepatic Cu concentration, which may be due to Cu being taken up in lysosomes to prevent oxidative damage when hepatocellular Cu concentration reaches a critical threshold . These results suggest that more studies are needed to investigate the impacts of hepatic Cu concentration on other measures of liver damage and function as well as animal health and production.…”
Section: Copper and Livestockmentioning
confidence: 99%
See 3 more Smart Citations